2021
DOI: 10.1002/ppul.25320
|View full text |Cite
|
Sign up to set email alerts
|

Clinical validation of a mandibular movement signal based system for the diagnosis of pediatric sleep apnea

Abstract: Background Given the high prevalence and risk for outcomes associated with pediatric obstructive sleep apnea (OSA), there is a need for simplified diagnostic approaches. A prospective study in 140 children undergoing in‐laboratory polysomnography (PSG) evaluates the accuracy of a recently developed system (Sunrise) to estimate respiratory efforts by monitoring sleep mandibular movements (MM) for the diagnosis of OSA (Sunrise™). Methods Diagnosis and severity were defined by an obstructive apnea/hypopnea index … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 43 publications
0
3
0
1
Order By: Relevance
“…This device may be convenient and promising as a home-based modality, providing a simplified diagnostic approach for pediatric sleep apnea, however, this will need additional validation to thoroughly evaluate its diagnostic accuracy in unattended home settings. 27 These studies demonstrate the growing interest in using at-home devices for monitoring pediatric sleep disorders, particularly in the context of SDB and OSA. While telehealth-supported level 2 PSG has shown promise as a lower-cost and more accessible alternative to traditional level 1 PSG, further validation studies may be necessary before it can be considered a standard diagnostic tool.…”
Section: Home Diagnostic Approachesmentioning
confidence: 82%
See 2 more Smart Citations
“…This device may be convenient and promising as a home-based modality, providing a simplified diagnostic approach for pediatric sleep apnea, however, this will need additional validation to thoroughly evaluate its diagnostic accuracy in unattended home settings. 27 These studies demonstrate the growing interest in using at-home devices for monitoring pediatric sleep disorders, particularly in the context of SDB and OSA. While telehealth-supported level 2 PSG has shown promise as a lower-cost and more accessible alternative to traditional level 1 PSG, further validation studies may be necessary before it can be considered a standard diagnostic tool.…”
Section: Home Diagnostic Approachesmentioning
confidence: 82%
“…The study found that the Sunrise MM device offered a balanced accuracy of 85% and an area under the receiver operating characteristic curve (ROC AUC) of 0.9 for AHI > 5 events per hour, making this device a viable option for the detection of children with moderate to severe OSA. This device may be convenient and promising as a home‐based modality, providing a simplified diagnostic approach for pediatric sleep apnea, however, this will need additional validation to thoroughly evaluate its diagnostic accuracy in unattended home settings 27 . These studies demonstrate the growing interest in using at‐home devices for monitoring pediatric sleep disorders, particularly in the context of SDB and OSA.…”
Section: Diagnosis Of Sdb: Beyond the Ahimentioning
confidence: 97%
See 1 more Smart Citation
“…12 Another study using this technology coupled with automated analysis conducted in the pediatric population also demonstrated a good agreement between MJM and the polysomnographic results. 13 The PSG is also the reference technique for the evaluation of treatment efficacy and residual events in children treated by continuous positive airway pressure (CPAP) or noninvasive ventilation (NIV). The management of OSA in children is essentially based on the treatment of the underlying cause of obstruction (tonsillectomy or maxilla facial surgery, orthodontic management, allergy management, weight loss in case of obesity).…”
Section: Introductionmentioning
confidence: 99%
“…importantes que dans la population adulte. Ce diagnostic dérivant de l'analyse du MM se montre favorable dans les formes modérées à sévères, ne montrant qu'une sensibilité et une spécificité médiocres dans les formes légères9 . D'autres études essaient de pousser l'algorithme plus loin, dont l'étude de Le-Dong et al (2021) qui étudie le lien entre le MM et les différents stades du sommeil, avec des résultats prometteurs 10 .…”
unclassified